Power Quality Improvement Based on Active Harmonic Filter in 24 kV Liquefied Natural Gas Industrial Plant’s Photovoltaic System - Pothisarn, Chaichan; Patcharoen, Theerasak; Lothongkam, Chaiyaporn; Ngaopitakkul, Atthapol; Lertwanitrot, Praikanok; Ananwattanaporn, Santipont (My University, 2026)
This paper presents a case study demonstrating the power quality improvements in a 24 kV distribution system at a liquefied natural gas (LNG) industrial plant with variable speed drives (VSDs), the conventional capacitor bank, and a rooftop solar photovoltaic system. Solar photovoltaic (PV) inverters can supply harmonic currents to the grid, potentially affecting the system and causing maloperation of sensitive equipment in both the utility systems and neighboring industries connected to it. Therefore, the installation of shunt active power filters (APFs) in a 400 V system was proposed in this study. The installed locations were varied, and the corresponding power qualities were analyzed. The results were examined in terms of design and harmonic elimination. Simulations were conducted using the PSCAD/EMTDC software version 4.5. The power quality simulation and field measurement results after the APF installation were compared to demonstrate the effectiveness of the proposed solutions. The addition of APFs was found to improve the power quality. In addition to the mechanism analysis, the economic feasibility of the proposed approach was investigated. The costs of APF installation in various locations were analyzed. The results show that the proposed method can improve the power supply at a reasonable price. This work contributes to sustainable industrial energy systems by improving the reliability and power quality of photovoltaic-integrated electrical networks, thereby supporting higher penetration of renewable energy resources and stable low-carbon industrial operation.
Keywords: active power filter; economic feasibility; rooftop solar photovoltaic system; sustainable energy systems; total harmonic distortion